Pedagogical Articles of Lev Tolstoy as a Source of Research Problems Psychological and Educational Characteristics of the Individual Student - Oleksandr Mikhno (Pedagogical Discourse, 2013)
The  pedagogical articles of Lev Tolstoy, containing some of the earliest attempts to explore the history of pedagogy are analyzed and the psychological and pedagogical features of schoolchildren is described. An individual approach to Yasnaya Polyana school students is traced and the following characteristics of the elements: imagery, psychology, attention to the emotional qualities of the pupil are identified. It is proved that the teaching of Lev Tolstoy articles are relevant sources of historical and pedagogical research problems of psychological and pedagogical characteristics of the individual student.